Implementation of Money Laundering Investigation Policy with Tax Crimes as Predicate Offenses at the Directorate General of Taxes - Dian Wahyudin (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
(Implementasi Kebijakan Penyidikan Tindak Pidana Pencucian Uang dengan Pidana Asal Tindak Pidana dibidang Perpajakan di Direktorat Jenderal Pajak) The widespread occurrence of tax-related criminal offenses committed by taxpayers has resulted in substantial losses to state revenue. In response, the Directorate General of Taxes (DGT) has adopted the policy of investigating money laundering offenses as an instrument to create deterrence and fear effects for non-compliant taxpayers, while simultaneously safeguarding state revenue losses arising from tax crimes. This study aims to examine and analyze the implementation of the money laundering investigation policy at the Directorate General of Taxes and to assess its impact on the recovery of losses to state revenue. This research employs a descriptive qualitative method using goal-oriented, source-based, and process-based approaches. Data were collected through literature review, in-depth interviews, observation, and documentation analysis. The findings reveal that the implementation of the money laundering investigation policy at the Directorate General of Taxes is consistent with policy implementation theory, as it demonstrates the presence of clear policy objectives, implementation activities, measurable outcomes, and post-implementation evaluation. However, from the perspective of the number of cases handled and the value of recovered state revenue, the impact of money laundering investigations has not yet been significant. This condition arises because perpetrators of tax crimes tend to prefer restorative justice settlement mechanisms by restoring state revenue losses along with administrative sanctions, thereby avoiding exposure to money laundering investigations. Nevertheless, money laundering investigations remain strategically important as a deterrence mechanism that encourages compliance and supports the recovery of state revenue. Abstrak Maraknya tindak pidana dibidang perpajakan yang dilakukan wajib pajak mengakibatkan kerugian negara yang sangat besar. Salah satu kebijakan yang dikeluarkan oleh Direktorat Jenderal Pajak untuk menimbulkan efek jera dan efek gentar kepada wajib pajak yang tidak patuh serta upaya menyelamatkan kerugian pada pendapatan negara akibat tindak pidana perpajakan adalah dengan melakukan penyidikan Tindak Pidana Pencucian Uang. Tujuan penelitian ini adalah untuk mengetahui dan menganalisa implementasi kebijakan penyidikan Tindak Pidana Pencucian Uang  di  Direktorat  Jenderal  Pajak  serta  dampaknya  terhadap  pengembalian kerugian pada pendapatan negara. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan sasaran, pendekatan sumber dan pendekatan proses melalui kegiatan studi kepustakaan, wawancara, observasi dan dokumentasi data. Hasil penelitian menunjukkan bahwa Implementasi Kebijakan Penyidikan Tindak Pidana Pencucian Uang di Direktorat Jenderal Pajak telah sesuai dengan dengan teori implementasi kebijakan yaitu adanya tujuan sasaran kebijakan, adanya aktivitas kegiatan, adanya hasil dari kegiatan dan adanya analisa kembali. Kebijakan Penyidikan Tindak Pidana Pencucian Uang di Direktorat Jenderal Pajak belum berdampak signifikan dari perspektif jumlah perkara yang ditangani dan nilai recovery kerugian negara karena pelaku tindak pidana di bidang perpajakan lebih memilih opsi penyelesaian restorative justice dengan mengembalikan kerugian negara berikut sanksinya agar terhindar dari penyidikan Penyidikan Tindak Pidana Pencucian Uang.